Preparation and characterization of plasticized Polylactic acid/starch blend - Jame, Raina; Mirghani, Mohamed Elwathig Saeed; Anuar, Hazleen; Samat, Noorasikin; Ali, Fathilah (2015)
Petroleum based packaging materials has raised environmental concerns due to its non-environmentally friendly degradation. Conventional plastic takes a long time to degrade and remains in the waste dump. Since then, attention to biodegradable plastics has been heightened for its greener degradation. Polylactic acid (PLA) is a renewable polymer with mechanical properties comparable to those of the conventional plastics. This study aims to improve the mechanical and thermal properties and reducing the cost of PLA production by blending PLA with starch as filler and epoxy palm oil (EPO) as plasticizer. The PLA/starch/EPO blends were prepared by solution casting and melt blending methods and properties of the blends were studied and characterized. The thermal properties of plasticized PLA/starch were investigated by Differential Screening Calorimetry (DSC) followed by Fourier Transform Infra-Red Spectroscopy (FT-IR) in order to observe the degree of interaction of plasticized PLA/starch blend. The mechanical properties were investigated using Universal Tensile Test.